The Influence of Family Communication, Environment and Youtube Media on the Islamic Character of Children - Galang Surya Adi Pratama; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2021)
The formulation of the problems contained in this study are a) How is the influence of family, environment and YouTube media simultaneously on the Islamic character of children? And b) How is the influence of family communication, environment and YouTube media partially on the Islamic character of children?. The type of research used is quantitative, the sample used as research is 109 children, the sampling technique used is simple random sampling, the data collection technique uses a questionnaire, the data analysis technique uses multiple linear regression with the help of the IBM SPSS Statistics 20 application. simultaneously between the variables of family communication, environment and YouTube media on the Islamic character of children. And there is a partial effect of each variable (family communication, environment and youtube) on the child's Islamic character variable.